An innovative model of supply chain management: a single case study in the electronic sector. (29th December 2008) - White, A.D.; Mohdzain, M.B.
This paper will report and analyse a case study on the utilisation of information systems by one of the largest global manufacturers of high-technology/electronic products. It will focus on their adoption of the services of an electronic marketplace called E2open and is based on 12 semistructured interviews undertaken with both organisations. The paper will make three contributions. It will firstly show how a new type of organisational entity is emerging, which challenges the validity of current ontologies for the organisational actors within the supply chain. Secondly, it will consider how the connectivity between buyer and supplier may be following a similar pattern to the transportation of material goods between these entities, in that it is emerging as an activity that will increasingly be managed by a third party. Finally, it will show how the use of the application service provider model of software provision is being used to enable the development of information systems which manage the supply chain and not just the operations of individual organisations. The extant theory will then be used to interpret the findings, as well as eliciting from the findings what the implications of this case are for further research in this field and for supply chain managers.